2020
DOI: 10.3389/fmed.2020.584036
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Heat and Humidity-Based Treatment for the Reuse of Personal Protective Equipment: A Pragmatic Proof-of-Concept to Address the Mass Shortage of Surgical Masks and N95/FFP2 Respirators and to Prevent the SARS-CoV2 Transmission

Abstract: Background: The coronavirus infectious disease-2019 (COVID-19) pandemic has led to an unprecedented shortage of healthcare resources, primarily personal protective equipment like surgical masks, and N95/filtering face piece type 2 (FFP2) respirators. Objective: Reuse of surgical masks and N95/FFP2 respirators may circumvent the supply chain constraints and thus overcome mass shortage. Methods, design, setting, and measurement: Herein, we tested the effects of dry-and moist-air controlled heating treatment on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In principle, this first washing step should be sufficient to eliminate the microorganisms that are present on the masks. Nonetheless, in the special case of a pandemic, especially for a virus pandemic, it is important to reduce the contamination risk to ensure a health and safety state ( Bernard et al, 2020 ). Moreover, the analysis of the variability of the cleanliness of washed masks suggest that a safety state is not achieved by a washing step procedure using masks coming from the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, this first washing step should be sufficient to eliminate the microorganisms that are present on the masks. Nonetheless, in the special case of a pandemic, especially for a virus pandemic, it is important to reduce the contamination risk to ensure a health and safety state ( Bernard et al, 2020 ). Moreover, the analysis of the variability of the cleanliness of washed masks suggest that a safety state is not achieved by a washing step procedure using masks coming from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences for that pattern of usage led to a reduced breathability in the masks and the possibility for germs to translocate. Indeed, sub-optimal recycling procedures consisted of disinfection without any cleaning step ( Liao, 2020 , Ibáñez-Cervantes et al, 2020 ; Cai and Floyd, 2020 ; Cheng et al, 2020 ; Bernard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 pandemic resulted in a huge increase in demand for Personal Protective Equipment (PPE), three times the number of respirators and six times that of surgical mask [ 19 ]. Thus, at the beginning of this pandemic, several countries and health facilities were suffering from in- and out-hospital mass shortage of protective FFP2 respirators [ 7 ]. This rise in demand has also resulted in unsuitable PPE being sold that are unfit for use as they do not meet international standards or national legislation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microwave-generated steam was shown to be effective in FFP2 decontamination but also incompatible with some kind of respirators, due to arcing observed around some types of metal nose clips and by loss of adhesion of clips to the mask [ 22 ]. One-hour treatment in a climate chamber at 70 °C with 75% humidity rate was shown to be adequate for enabling substantial decontamination of FFP2s [ 7 ]. Recent literature reviews concluded that the evidence supporting appropriate decontamination strategies for FFP2 respirators remains scarce, although ultraviolet irradiation and vaporized hydrogen peroxide seem to be the current recommended standard [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation